Peran Keluarga dalam Perawatan Penderita Diabetes Melitus secara Mandiri di Rumah - Sundari, Sri; Setyawati, Ika (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2006)
The role of family in the management of diabetic patients is needed to minimize the complication and improve the blood glucose level. The objective ofthe research was to identify the role offamily in self-care of diabetic patients at home. It was a retrospective descriptive study using a cross-sectional design.The research subjects were family members of diabetic patients who accompanied patients coming to Internal Medicine Polyclinic, General Hospital ofPKU Muhammadiyah Yogyakarta from 22 September to 28 October 2005. The research sample was 50 respondents who were selected with a purposive sampling technique. Data was collected using a questionnaire. Data analysis used a formula ofP = â X100% and the results were categorized into good, fair, unfavorable, and poor.The research revealed that the role offamily in self-care of diabetic patients at home which was considered as good was 58%. The role of the family included aspects of patient education (100%), food planning (66%), exercises (56%), pharmacological therapy (68%), and diabetic foot care (42%). Similarly, the self-management of diabetic patients at home which was considered as good was 58%. The findings showed that the role of the family is important in self-care ofdiabetic patients at home. This is importantfor health care providers to advocate the patientâs family to actively participate in care giving and motivating the diabetic patients in self-care at home.Peran keluarga dalam perawatan penderita diabetes melitus diperlukan untuk meminimalkan terjadinya komplikasi dan memperbaiki kadar glukosa darah. Tujuan penelitian adalah untuk mengetahui peran keluarga dalam perawatan penderita diabetes melitus secara mandiri di rumah.Jenis penelitian adalah deskriptif retrospektif dengan pendekatan cross-sectional. Subyek penelitian adalah anggota keluarga klien yang mendampingi ke poliklinik penyakit dalam RSU PKU Muhammadiyah Yogyakarta pada tanggal 22 September sampai dengan 28 Oktober2005. Jumlah sampel adalah 50 responden dengan teknik purposive sampling. Pengumpulan data dengan kuesioner. Analisis data dengan menggunakan rumus P = â x 100% hasilnya dikategorikan menjadi baik, cukup baik, kurang baik, dan tidak baik.Hasil penelitian menunjukkan peran keluarga dalam perawatan penderita DM secara mandiri di rumah yang dikategorikan baik adalah 58%. Peran keluarga tersebut dibagi dalam aspek penyuluhan 100%, perencanaan makan 66%, latihan jasmani 56%, terapi farmakologi 68%, dan perawatan kaki diabetes 42%, sedangkan pengelolaan penderita diabetes melitus secara mandiri di rumah yang dikategorikan baik adalah 58%. Hasil penelitian menunjukkan peran keluarga penting dalam merawat penderita DM secara mandiri di rumah karena keluargapenderita DM perlu berperan aktif dalam merawat dan memotivasi penderita DM dalam perawatan mandiri di rumah.